Alibaba: the company that made eBay a dwarf - Shen, Xiaobai (Henry Stewart Talks, 2016)
This case study discusses the e-commerce company Alibaba as an example of innovative imitation in China. Alibaba reinvented the technology of eBay’s online selling platform to include ingenious features such as a fraud-averting pay system. These features, and the consequent mega-success of Alibaba, exemplify the ability of Chinese companies to put their user’s needs and concerns at the center of their products.